Benefits of Ga, Ge and As substitution in Li2FeSiO4: a first-principles exploration of the structural, electrochemical and capacity properties. Issue 26 (23rd June 2020) - Yan, Xiaotong; Hou, Yuhua; Zheng, Shouhong; Huang, Youlin; Li, Wei; Shi, Zhiqiang; Tao, Xiaoma
Abstract : Herein, the feasibility of Fe substitution by Ga, Ge and As in Li2 FeSiO4 in modulating its structural, mechanical, electrochemical, capacity and electronic properties was systematically studied via first-principles calculations based on density functional theory within the generalized gradient approximation with Hubbard corrections (GGA+ U ). Abstract : Herein, the feasibility of Fe substitution by Ga, Ge and As in Li2 FeSiO4 in modulating its structural, mechanical, electrochemical, capacity and electronic properties was systematically studied via first-principles calculations based on density functional theory within the generalized gradient approximation with Hubbard corrections (GGA+ U ). The calculated results show that Ga, Ge and As doping can effectively reduce the range of the cell volume change during Li + removal, improving the Li + detachment ability and cycle stability of the system. Meanwhile, the calculated mechanical properties including modulus ratio, B/G, and Poisson ratio, ν, indicate that the doped systems of Ga, Ge and As exhibit excellent mechanical properties. In addition, besides the increase in theoretical average deintercalation voltage induced by the Ga dopant when more than one Li + ion is removed in the formula unit, the doping of Ga, Ge and As all reduce the theoretical average deintercalation voltage in the process of Li + extraction. Especially in the case of doping of Ge, when 0.5 Li + is removed from LiFe0.5 Ge0.5 SiO4, the theoretical average deintercalation voltage only increases by 0.19 V compared with the case of the removal of one Li + in Li2 Fe0.5 Ge0.5 SiO4, which causes the cathode material to have a longer and more stable discharge platform. Moreover, in the process of Li + removal, the doping of Ga, Ge and As can effectively participate in the charge compensation of the system, and Ge and As can provide further charge, increasing the capacity of the Li2 FeSiO4 cathode material considerably.